2018
DOI: 10.1108/qmr-10-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

“A feminine brand? Never!” Brands as gender threats for “resistant” masculinities

Abstract: Purpose The purpose of this paper is to examine the relationships between men and brands and specifically how they configure their masculinities in relation to daily used brands. Design/methodology/approach In-depth interviews with projective technique were conducted with 20 men with different masculinities and sexual orientations to explore their practices regarding and relations to various product categories and brands. Findings First, this paper shows how men’s relationships to daily used brands vary ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…Regarding the topic of femvertising, consumers consider it is positive to bring up feminist issues and fight against gender stereotypes and sexism in advertising, with positive consumer reactions in terms of brand attitude (Abitbol and Sternadori, 2016). However, brands that are considered feminine due to their communication strategy may be avoided by men with traditional masculinities even though the product may be unisex (Ulrich and Tissier-Desbordes, 2018).…”
Section: Femvertisingmentioning
confidence: 99%
“…Regarding the topic of femvertising, consumers consider it is positive to bring up feminist issues and fight against gender stereotypes and sexism in advertising, with positive consumer reactions in terms of brand attitude (Abitbol and Sternadori, 2016). However, brands that are considered feminine due to their communication strategy may be avoided by men with traditional masculinities even though the product may be unisex (Ulrich and Tissier-Desbordes, 2018).…”
Section: Femvertisingmentioning
confidence: 99%
“…Previous studies have examined the effects demographic characteristics have on consumer preferences. Specifically, previous research has found that consumers prefer products that are congruent with their gendered identities (Gal & Wilkie 2010;Neale et al, 2016;Ulrich & Tissier-Desbordes, 2018;Worth et al, 1992), cultural characteristics (Hillman, 1979;Rozin, 1988), and education (Mielby et al, 2013;Cavaliera & Ventura, 2018). For example, researchers found that individuals' education levels influence general dispositions towards innovation in the foods.…”
Section: Influences Of Individual Characteristics On Consumer Preferementioning
confidence: 99%
“…An alternative approach to studying brand gender, specifically brand masculinities, draws upon a transactional/subjectivist epistemology, looking at brand masculinities as co-constructed (Gee & Jackson, 2012;Hirschman, 2014, Strate, 1992Ulrich & Tisier-Desbordes, 2018). This can be seen in Holt (2003), who explores the constructions of masculinities in beer brands and argues that products serve as vehicles through which target consumers experience gender myths (i.e., the configurations/commonsense of masculinities).…”
Section: Brand Gender Approaches: Brand Masculinitymentioning
confidence: 99%
“…[this] allows us to convince ourselves (and perhaps others) that we can be a different person than we would be without them" (Belk, 1988, p. 145). Furthermore, much work has acknowledged that the gendering of brands is an essential strategy for projecting brand characteristics and potentially increasing sales (Aaker, 1997;Nelson & Hye-Jin, 2008;Siripai & Haywood, 2017, Ulrich & Tisier-Desbordes, 2018.…”
mentioning
confidence: 99%